Arabic Language Learning Strategies among Malaysian Students at Yarmouk University as Related to the Variables of Specialization and Gender - Al-Khawaldeh, Mohammed (Jordan Journal of Educational Sciences, 2015)
This study aimed at investigating the level of using Arabic language learning strategies among Malaysian students at Yarmouk University, and whether there would be statistical significant differences at the level (α = 0.05) in their using of these strategies due to the variables of: student’s specialization, and gender. To achieve the aims of the study an (Oxford, 1990) foreign language learning strategies scale was used. The scale consisted of (50) items distributed on memory, cognitive, metacognitive, compensation, affective and social strategies. (210) undergraduate male female Malaysian students who study Arabic language and Alsharea specializations at Yarmouk University participated in the study at the end of 2nd semester 2013/2014. The results of the study revealed that the level of using Arabic language learning strategies as a whole was moderate, with different levels on the six strategies as follows: Compensation and social strategies with high level, metacognitive, cognitive, memory and affective strategies with moderate level. The results also revealed that there were statistical significant differences in their using strategies due to the variables of specialization in favor of the Arabic language, and gender in the favor of the females